CTNI-63. PROGNOSTIC FACTORS IN PATIENTS WITH BASAL GANGLIA GERM-CELL TUMORS: A RETROSPECTIVE ANALYSIS OF THE SINGLE CHINESE INSTITUTE EXPERIENCE FROM 2009 TO 2019 - Hu, Qingjun (Neuro Oncol, 2020)
OBJECTIVE: To evaluate the clinical factors related to the prognosis of basal ganglia germ cell tumors. METHODS: A retrospective analysis of 52 cases of the basal ganglia germ cell tumors treated from January 2009 to January 2019 in the department of oncology of Guangdong Sanjiu Brain Hospital. The median age: 12 years (range: 5–32), The median course of disease: 11.7 months (range: 1–54). Thirteen cases were diagnosed by biopsy and 39 cases were diagnosed by elevated tumor markers. There were 31 patients (59.6%) diagnosed with germinomas and 21 patients (40.4%) with non-germ germ cell tumors. Univariate and multivariate survival analysis was performed. RESULTS: To October 15, 2019, the median follow-up time was 30.4 months (range 2–124 months). The 5-year survival rate was 85%, and the 5-year progression-free survival rate was 84%. Multivariate analysis found whether serum AFP was greater than 100mIU / ml, (with HR: 11.441,95% CI: 2.09–47.66, P = 0.005),the degree of surgical resection(with HR 5.323 (1.19–23.812), P = 0.029), PD as the effect of radiotherapy (HR: 16.53, (1.19–23.81), P = 0.001) were independent prognostic factor affecting survival. CONCLUSION: The pathological type, degree of surgical resection, and response to initial treatment can all affect survival.